SOCIO-PRENEURSHIP AS A DRIVER FOR SUSTAINABLE DEVELOPMENT MEASURING THE COMMUNITY-LEVEL ECONOMIC IMPACT OF RURAL ECOTOURISM INITIATIVES - Tran Thi Lan; Nong Chai; James Njoroge (Yayasan Adra Karima Hubbi, 2025)
Rural communities often face economic challenges such as unemployment and limited income sources, making sustainable development a complex issue. Socio-preneurship, which combines social entrepreneurship with sustainable business practices, has emerged as a powerful model to address these challenges. Rural ecotourism initiatives, as a form of socio-preneurship, have gained attention for their potential to stimulate local economies, preserve natural resources, and promote social well-being. This study examines the community-level economic impact of rural ecotourism, focusing on how these initiatives contribute to income generation, job creation, and local business growth. Using a mixed-methods approach, this research combines quantitative surveys and qualitative case studies to assess the economic effects of rural ecotourism in three rural communities. The study measured indicators such as household income, business revenue, and job creation. The results show that 72% of households reported income increases, 65% of local businesses experienced revenue growth, and 48% of respondents identified job creation in the ecotourism sector. The findings indicate that rural ecotourism can drive sustainable economic development by diversifying local economies and creating long-term job opportunities. These initiatives also foster socio-economic resilience in rural areas. The study highlights the importance of community engagement in ensuring the success of ecotourism projects and suggests that socio-preneurship can be a viable strategy for rural development.